Pleasures of Skill and Moral Conduct - Armin Falk; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper provides controlled experimental evidence that striving for pleasures of skill can have negative moral consequences and causally reduce moral values. Subjects perform an IQ-test. They know that each correctly solved question increases the likelihood of moral transgression. In terms of self-image, this creates a trade-off between signaling excellence and immoral disposition. We contrast performance in the IQ-test to test scores in an otherwise identical test, which is, however, framed as a simple questionnaire. We find that subjects perform significantly better in the IQ-test condition, and become less willing to reduce test scores in order to act morally.
Keywords: C91; D02; D62; 330